Two Clusters of Fluoroquinolone and Clindamycin-Resistant Clostridium difficile PCR Ribotype 001 Strain Recognized by Capillary Electrophoresis Ribotyping and Multilocus Variable Tandem Repeat Analysis - Nyc, Otakar; Tejkalova, Renata; Kriz, Zdenek; Ruzicka, Filip; Kubicek, Lubos; Matejkova, Jana; Kuijper, Ed; Krutova, Marcela (Microbial drug resistance (Larchmont, N.Y.), 2017)
AIM: To perform a retrospective analysis of the high occurrence of Clostridium difficile infection in the surgical department of a Czech tertiary care hospital and to identify weaknesses in C. difficile infection (CDI) prevention and control policies. METHODS: Clinical and epidemiological data on eleven CDI cases were collected. C. difficile isolates were characterized by capillary electrophoresis ribotyping, multilocus variable tandem repeat analysis (MLVA), gyrA gene fragment sequencing, and erm(B) fragment PCR amplification. Antibiotic susceptibility to metronidazole, vancomycin, ciprofloxacin, moxifloxacin, and clindamycin was tested. FINDINGS: Eleven CDI cases were caused by C. difficile PCR ribotype 001 strains. These strains revealed two different MLVA profiles with 11 tandem repeat differences. All isolates were susceptible to metronidazole and vancomycin and resistant to ciprofloxacin (MIC ≥32 mg/L), moxifloxacin (MIC ≥32 mg/L), and clindamycin (MIC ≥256 mg/L). All isolates revealed amino acid substitution Thr82Ile, in the GyrA and were erm(B) negative. CONCLUSION: Two fluoroquinolone and clindamycin-resistant C. difficile PCR ribotype 001 strain clusters occurred at one of the surgical departments of a tertiary care hospital. Ineffective decontamination with suboptimal concentration and time of exposure of sporicidal disinfectants may have resulted in C. difficile transmission.
Keywords: Microbial Sensitivity Tests; centra terciární péče; vankomycin; Amino Acid Substitution; Moxifloxacin; MLVA; exprese genu; DNA bakterií; Humans; Metronidazole; Ribotyping; klostridiové infekce; Gene Expression; mnohočetná bakteriální léková rezistence; Clindamycin; Methyltransferases; DNA gyráza; Multilocus Sequence Typing; capillary electrophoresis ribotyping; moxifloxacin; Electrophoresis, Capillary; antimicrobial drug resistance; Female; Aged; Fluoroquinolones; mikrobiální testy citlivosti; senioři; lidé; antibakteriální látky; Minisatellite Repeats; ribotypizace; Vancomycin; Drug Resistance, Multiple, Bacterial; minisatelitní repetice; elektroforéza kapilární; PCR ribotype 001; ciprofloxacin; DNA, Bacterial; ženské pohlaví; Anti-Bacterial Agents; Male; substituce aminokyselin; Retrospective Studies; Clostridium Infections; multilokusová sekvenční typizace; Ciprofloxacin; Czech Republic; klindamycin; DNA Gyrase; Tertiary Care Centers; retrospektivní studie; fluorochinolony; Česká republika; mužské pohlaví; methyltransferasy; Clostridium difficile; metronidazol; Thr82Ile; Clostridioides difficile